2003
DOI: 10.1212/01.wnl.0000078940.53438.83
|View full text |Cite
|
Sign up to set email alerts
|

A self-administered screener for migraine in primary care

Abstract: The three-item ID Migraine migraine screener was found to be a valid and reliable screening instrument for migraine headaches. Its ease of use and operating characteristics suggest that it could significantly improve migraine recognition in primary care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
514
2
10

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 488 publications
(566 citation statements)
references
References 54 publications
25
514
2
10
Order By: Relevance
“…Based on our data in this study the ID migraine questionnaire compared to the reported migraine had 85% sensitivity and 76% specificity to identify possible migraine, which is in a comparable range with the original validation study (Lipton et al 2003). …”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…Based on our data in this study the ID migraine questionnaire compared to the reported migraine had 85% sensitivity and 76% specificity to identify possible migraine, which is in a comparable range with the original validation study (Lipton et al 2003). …”
Section: Resultssupporting
confidence: 72%
“…The ID‐migraine questionnaire was used to collect information about headaches and especially migraine type headache symptoms in the past 3 months (Lipton et al 2003). The ID‐Migraine is a validated screening tool for migraine, which includes 3 items of the main migraine symptoms: nausea, photophobia and disability.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All women who participated in the questionnaire were classified in a pattern due to their history of headache as regards being pregnant: ''Only before pregnancy'' (pattern Yes/No), ''Both before and during pregnancy'' (pattern Yes/Yes), ''Only during pregnancy'' (pattern No/ Yes). The ID Migraine Screener test [1,2] was used to classify subjects in ''Definite migraine'' (3/3 positive answers), ''Probable migraine'' (2/3), ''Unlikely migraine'' (1/3), ''Other headaches'' (0/3).…”
Section: Discussionmentioning
confidence: 99%
“…Several other validated headache questionnaires exist, most of them constructed as screening instruments for migraine and consisting of 3-8 items based on the IHS criteria [11][12][13][14][15][16][17][18]. Lipton et al presented a very short screening questionnaire for migraine with only three items and were able to achieve a sensitivity of 0.81 and specificity of 0.75, with a kappa of 0.68 [14]. More detailed migraine questionnaires have been presented by Kallela et al [19] and Hagen et al [20].…”
Section: Discussionmentioning
confidence: 99%